Human Security and Empowerment in Asia Beyond the Pandemic - Caballero-Anthony, Mely; Mine, Yoichi; Ishikawa, Sachiko (Politics in Asia, 2024)
In the context of the COVID-19 pandemic, this edited volume revisits the framework of human security and development. It examines the protection-empowerment nexus as applied to various vulnerable groups and populations affected by the pandemic. While the conventional human security literature has focused on top-down protection, this book offers new perspectives on human security by exploring bottom-up empowerment from both theoretical and practical perspectives. It also encourages readers to rethink the agency of vulnerable people in addressing the challenges posed by the pandemic. Through eight case studies from Southeast Asia and Japan, the contributors to this book demonstrate the importance of empowerment in achieving human security. They focus on the responses of vulnerable groups and communities to multiple threats to their lives, livelihoods, and dignity. The chapters discuss key human security concerns, such as poverty, the environment, food, forced migration, gender, health, aging, peace, and justice - all of which have been compounded and exacerbated by the COVID-19 pandemic. An essential resource for students and scholars of human security in the aftermath of COVID-19 and its wider impacts.